Focus Marking via Gestures - Ebert, Cornelia; Evert, Stefan; Wilmes, Katharina (Proceedings of Sinn und Bedeutung, 2019)
This paper contributes to the recent investigations of speechaccompanying gestures under a formal semantic view. We show that gestures can serve to disambiguate a sentence with respect to its possible focus domains. We provide a statistical evaluation of data gained from a corpus annotated with gestures and information structure. The language under investigation is German. We argue that a sentence that, in isolation, is ambiguous concerning the extension of its focus domain is disambiguated via speech-accompanying gestures. Gesture thus is a means to mark information structure next to intonation and word order.